THE RELATIONSHIP BETWEEN KNOWLEDGE LEVELS AND CERDIK BEHAVIOR IN HYPERTENSION PATIENTS DURING THE COVID 19 PANDEMIC IN THE COMMUNITY RT 011 PLERED PURWAKARTA - Ma'arief, Syamsul; Indrawati, Lina; Pelawi , Arabta Malem Peraten (Rena Cipta Mandiri, 2024)
The presence of the Covid 19 pandemic certainly affects many aspects of people's lives, one of which is the health aspect, the number of cases of Covid 19 makes people feel worried, anxious, and stressed. This has resulted in people being afraid to check their health conditions to health services for the reason of being afraid of contracting covid 19, so that many diseases are not well controlled, one of which is hypertension. Hypertension is known as the Silent Killer because it often causes no symptoms until it becomes more serious. Hypertension is characterized by measurement results showing systolic blood pressure above 140 mmHg or diastolic blood pressure above 90 mmHg. The Indonesian government has given serious attention to the prevention and control of hypertension by holding the CERDIK behavior program, while CERDIK behavior is to check health regularly, get rid of cigarette smoke, be diligent in physical activity, diet, get enough rest and manage stress. The research method used is quantitative with cross-sectional analytic research. It was found that the value of 5% (0.05) Chi-Square Test results obtained p-value (0.000) < value (0.05) so that it can be concluded from these results H0 is rejected and Ha is accepted. This means that there is a relationship between the level of knowledge and CERDIK behavior in patients with hypertension during the covid 19 pandemic in the community RT 011 RW 03 Plered Purwakarta.